Problemy rozwoju gospodarczego państw nieuznawanych na przykładzie Abchazji (Politeja, 2018)
Problems of Economic Development of the Unrecognised State – the Case of AbkhaziaSince its inception as a result of the victorious war with Georgia, the de facto independent Abkhazia has been struggling with a deep economic crisis characterised by war damage, economic blockade and the lack of international recognition. The aim of this paper is to analyse the main problems and challenges of unrecognised states in the field of economic development on the example of the Republic of Abkhazia. The article summarises the economic consequences of the Georgian-Abkhazian conflict, characterises the economic development of Abkhazia in the post-war period and analyses the effects of the economic blockade as well as the economic effects of the support of the external patron (the Russian Federation).